Conservative Treatment of Closed Fracture Shaft Humerus in Adult Patients - Majeed, Ghadeer . H; Al- Iedani, Mohammed S.; Kalif, Ismaeel (AL-Kindy College Medical Journal, 2013)
Background: Fractures of the humeral shaft accounting for approximately 3% of all fractures. There is a wide array of good options for their treatment and controversy over the best methods. Although good techniques of osteosynthesis are available, the aim of this article is toemphasize on the benefit and good outcome of conservative treatment for properly selected cases to decrease the cost and avoid the complications of surgery.